Sectorial Labor Migration and Sustained Industrialization in the Japanese Development Experience - Zahn, Frank (The Review of Economics and Statistics, 1971)
The history of developing economnies indicates that rural-urban migration accompanies economic progress [2, 3, 8, 15]. The migration is considered to take place between the agricultural and industrial sectors as well as the farm and the city. In the Japanese development experience it would be inaccurate to label migration as a physical movement of labor to the city [11, 13]. The peasant was culturally tied to his rural surrounding by strong family ties. But certainly the migration can be labeled as one of moving the labor force out of agricultural and into industrial pursuits where the culturally immobile labor force resulted in rural location of many industries. An analysis of the economic determinants of the Japanese style of migration may shed some light on potential development strategy in terms of the effort required to achieve sustained industrialization, that is, a sustained rise in the industrial-agrarian labor and real output ratios. The theoretical models, which purport to explain the rural-urban migration where sectorial and location changes occur simultaneously, range from the simple wage differential models of Jorgenson [6], Lewis [7], and Ranis-Fei [11] to the more recent expectations models of Todaro [17] and Harris-Todaro [5]. The latter models stress the importance of both the income ratio and the probability of urban employment when analyzing the determinants of urban labor supplies. On the demand side, Eckaus' [4] famous factor proportions model is the most notable attempt to analyze the problem of labor absorption. In contrast, there have been few attempts to estimate a model reflecting the simultaneous impact of both supply and demand determinants of the distribution of labor between agricultural and industrial sectors. The objective of this paper is to construct and estimate a simple econometric model of the sectorial labor migration for a classic case of development, the Japanese economy. The basic sample on which the model is based extends from 1878 to 1937. The choice of Japan as a case study is predicated upon data availability [1, 9, 12] and recent interest in the development experience of that country. The interesting feature of the model is that it simultaneously considers the relative supply and relative demand determinants of the sectorial distribution of labor. Further, the dynamic properties of the model permit an analysis of the effort(s) required to achieve a sustained rise in the income and employment ratios which have been associated with economic progress through industrialization. In part II the basic model is specified, while in part III the Japanese economy is analyzed in terms of the basic model. In part IV the study is summarized and concluded.